Gut microbiota, inflammatory proteins, and allergic diseases - Hao Zhu; Minghang Dou; Xiangqun Jin (Medicine, 2026)
Some authors suggest a link between gut microbiota and allergic diseases; however, the genetically predicted relationship and the role of inflammatory proteins as mediators are still uncertain. Gut microbiota, inflammatory proteins, and 5 types of allergic diseases, namely allergic rhinitis (AR), atopic dermatitis, allergic conjunctivitis, food allergy, and asthma, were identified from large-scale genome-wide association studies summary data. In a 2-sample, bidirectional Mendelian randomization (MR) study, we systematically conducted 2980 primary tests (298 exposures tested bidirectionally against 5 allergic diseases). We used the inverse-variance weighted method as our primary estimator, with a prespecified false discovery rate threshold of q < 0.1 to identify robust associations. We further employed a 2-step MR and multivariable MR approach to test for potential mediation by inflammatory proteins. This study provides evidence of potential genetically predicted associations between specific gut microbiota, inflammatory proteins, and allergic diseases, along with exploratory mechanistic observations regarding mediation. These findings support that host-gut microbiota interactions may play a role in allergic disease susceptibility, although further validation using colocalization and cis-protein Quantitative Trait Locus analyses is required to establish clinical relevance. We identified numerous potential genetically predicted associations between the gut microbiota, inflammatory proteins, and the 5 allergic diseases. Notably, 2 of these associations remained robust after stringent false discovery rate correction and were identified as robust MR-supported associations. Specifically, a 1 standard deviation increase in genetically predicted relative abundance log-ratio of the species Collinsella aerofaciens was associated with a 23.5% higher risk of AR (odds ratio = 1.235, 95% confidence interval = 1.097–1.391, P = 4.83 × 10 −4 , adjust P = .098). Furthermore, genetically predicted higher levels of the CD40L receptor (CD40) were associated with a reduced risk of asthma (odds ratio = 0.939, 95% confidence interval = 0.906–0.974, P = 7.52 × 10 −4 , adjust P = .068). In exploratory mediation analyses, Fractalkine (CX3CL1) was found to potentially mediate the genetically predicted association between the genus Flavonifractor and AR (mediated proportion 18.5%; P = .024), and CD40 potentially mediated the genetically predicted association between the species Ruminococcus obeum and asthma (mediated proportion 11.02%; P = .046).